Atomic Layer Deposition Grown Titania Phases (TiO2, TiO, Ti2O) and its Influence on Water Splitting Electrocatalysis - Swaminathan, Jayashree; Palani, Parthiban; Salpekar, Devashish; Hernandez, Francisco Carlos Robles; Ashokkumar, Meiyazhagan; Ajayan, Pulickel M. (Advanced Sustainable Systems, 2025)
The systematic engineering of atoms and the precise tuning of their arrangement can unlock a range of hidden yet remarkable properties of materials. In this study, different phases of titanium oxide, including TiO2, TiO, and Ti2O, are developed using the Atomic Layer Deposition (ALD) technique. Notably, a novel TiO(2 )electride with a pbcn space group is identified, and variations in stoichiometries, such as Ti1.80O, Ti2.05O, and Ti2.30O, are observed through Rietveld analysis of the corresponding X-ray Diffraction (XRD) data. High-resolution transmission electron microscopy (HRTEM) imaging further revealed line defects such as stacking faults and edge dislocations in Ti2O. The interplay of stoichiometric defects in Ti2O electrides leads to tunable electrocatalytic behavior, enabling transitions from oxygen evolution to hydrogen evolution reactions. Importantly, using Density functional theory (DFT), Paterson analysis, and Fourier electron density mapping, the exceptional metallic properties of Ti2O are rationalized as arising from its unique spatial electron density distribution. Overall, this work underscores the significance of atomic-level structure engineering and opens the door to a new class of titanium oxide catalysts for electrochemical water splitting.
Keywords: atomic layer deposition; defect engineering; defect-rich titania; Electrocatalytic water splitting; Ti2O electrides

Study of magnetism and electrocatalytic properties in perovskite DyCrO3 - Ughade, Supriya; Singh, Dinesh; Poddar, Pankaj (Journal of Alloys and Compounds, 2025)
Uniformly sized perovskite DyCrO3 was synthesized by facile hydrothermal method. Complex interdependence of various parameters such as - pH, crystal growth duration, reaction temperature, precursor, and capping molecules on crystal growth was extensively investigated. The effect of synthesis parameters on the magnetic properties of hydrothermally synthesized DyCrO3 was compared with high-temperature synthesized DyCrO3. DyCrO3's potential for electrocatalytic water splitting in an alkaline medium (1.0 M KOH) was also evaluated. It demonstrates an overpotential of 280 mV for oxygen evolution reaction (OER) and 210 mV for hydrogen evolution reaction (HER). Further, it exhibits promising stability for OER and HER.
Keywords: DyCrO3; Electrocatalytic water splitting; Hydrothermal synthesis; magnetic property; perovskite